2022
DOI: 10.3390/molecules27175594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Tanshinone against Prostate Cancer

Abstract: Prostate cancer (PCa) is the most common malignant tumor of the male urinary system in Europe and America. According to the data in the World Cancer Report 2020, the incidence rate of PCa ranks second in the prevalence of male malignant tumors and varies worldwide between regions and population groups. Although early PCa can achieve good therapeutic results after surgical treatment, due to advanced PCa, it can adapt and tolerate androgen castration-related drugs through a variety of mechanisms. For this reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 172 publications
0
10
0
Order By: Relevance
“…Among them, the cell tumor antigen p53 (TP53), myc proto-oncogene protein (myc), transcription factor AP-1 (JUN), Proto-oncogene tyrosine-protein kinase SRC(SRC), caspase-3 (CASP3), and epidermal growth factor receptor(EGFR) play a key role in the anti-HCC process of TsIIA. In addition, previous studies have confirmed that TsIIA, as a fat-soluble polyphenol, can enter cells directly through the cell membrane due to its fat-soluble property and rely on the direct combination of the D ring in the molecular structure of TsIIA with the groove in the DNA molecule, thus interfering with the synthesis and transcription of DNA and thus exerting the anti-tumor effect ( 53 ). This is consistent with our results.…”
Section: Network Pharmacological Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Among them, the cell tumor antigen p53 (TP53), myc proto-oncogene protein (myc), transcription factor AP-1 (JUN), Proto-oncogene tyrosine-protein kinase SRC(SRC), caspase-3 (CASP3), and epidermal growth factor receptor(EGFR) play a key role in the anti-HCC process of TsIIA. In addition, previous studies have confirmed that TsIIA, as a fat-soluble polyphenol, can enter cells directly through the cell membrane due to its fat-soluble property and rely on the direct combination of the D ring in the molecular structure of TsIIA with the groove in the DNA molecule, thus interfering with the synthesis and transcription of DNA and thus exerting the anti-tumor effect ( 53 ). This is consistent with our results.…”
Section: Network Pharmacological Analysismentioning
confidence: 96%
“…Interestingly, TsIIA has significant antioxidant activity. From the structure of TsIIA, the antioxidant effect of TsIIA mainly depends on the D-ring (furan or dihydrofuran), and the structural change of the D-ring will also affect the antioxidant capacity ( 53 ). Secondly, TsIIA can also significantly increase the expression and activity of antioxidant enzymes, such as catalase (CAT), superoxide dismutase (SOD), and glutathione-S-transferase (GST).…”
Section: Liver Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Modern pharmacological studies have shown that all of the aforementioned components have reduced chemotherapy side effects and enhanced immunity. 24,25 Despite the outstanding clinical effectiveness of CLG, its mechanism of action must continue to be investigated. Therefore, the role of the PI3K/Akt/mTOR signaling pathway in the effect of CLG on CRC in nude mice was investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Other components comprise cryptotanshinone (0.55 mg/mL), diosgenin (0.58 mg/mL), 9‐Oxo‐10(E),12(E)‐octadecadienoic acid (0.18 mg/mL), adenosine (0.56 mg/mL), and emodin (0.39 mg/mL) 23 . Modern pharmacological studies have shown that all of the aforementioned components have reduced chemotherapy side effects and enhanced immunity 24,25 . Despite the outstanding clinical effectiveness of CLG, its mechanism of action must continue to be investigated.…”
Section: Introductionmentioning
confidence: 99%